2017
DOI: 10.1167/iovs.16-20211
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Differences Between Femtosecond Lenticule Extraction (FLEx) and Small Incision Lenticule Extraction (SmILE) Tested by 2D-Extensometry in Ex Vivo Porcine Eyes

Abstract: Citation: Spiru B, Kling S, Hafezi F, Sekundo W. Biomechanical differences between femtosecond lenticule extraction (FLEx) and small incision lenticule extraction (SmILE) refractive procedures tested by 2D-extensometry in ex vivo porcine eyes. Invest Ophthalmol Vis Sci. 2017;58:259158: -259558: . DOI:10.1167 PURPOSE. To evaluate the biomechanical stability of ex vivo porcine corneas after femtosecond lenticule extraction (FLEx) and small incision lenticule extraction (SmILE) refractive surgeries.METHODS. Forty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…Exponential model [5, 7, 26, 27] and Prony model [32, 33] have been found to well characterize corneal stress-strain data and stress relaxation data, respectively. From Table 2 and Table 3, the goodness-of-fit (R 2 ) for the two linear fittings, exponential fitting, and Prony model fitting was larger than 0.92, 0.98, 0.99, and 0.99, respectively, which indicated that our fitting methods were effective.…”
Section: Discussionmentioning
confidence: 99%
“…Exponential model [5, 7, 26, 27] and Prony model [32, 33] have been found to well characterize corneal stress-strain data and stress relaxation data, respectively. From Table 2 and Table 3, the goodness-of-fit (R 2 ) for the two linear fittings, exponential fitting, and Prony model fitting was larger than 0.92, 0.98, 0.99, and 0.99, respectively, which indicated that our fitting methods were effective.…”
Section: Discussionmentioning
confidence: 99%
“…However, these results should be interpreted with caution as the orientation of the collagen fibrils and the pressure induction in strip extensiometry are not similar to the intact eye. Furthermore, another and similar ex vivo strip extensiometry study of porcine eyes treated with SMILE and FLEX suggests that SMILE may be superior in terms of biomechanical stability after surgery [ 52 ].…”
Section: The Corvis St: Lasik Versus Smilementioning
confidence: 99%
“…Although this has not been documented in vivo , recent ex vivo porcine studies suggest superiority of the SMILE technique in preserving corneal stability when compared to the FLEx technique, (Spiru et al. ). The depth at where the refractive cut is placed is also a significant factor in accordance with the corneal structural differences, after both flap‐ and cap‐based procedures.…”
Section: Discussionmentioning
confidence: 99%